How to take into account exposure to drugs over time in pharmacoepidemiology studies of pregnant women?†. Issue 7 (27th March 2016) - Hurault‐Delarue, Caroline; Chouquet, Cécile; Savy, Nicolas; Lacroix, Isabelle; Beau, Anna‐Belle; Montastruc, Jean‐Louis; Damase‐Michel, Christine
Abstract: Purpose: The aim of this study was to develop a new pharmacoepidemiological method to take into account intensity and evolution of drug exposure, applied to pregnant women. Methods: Pregnant women were classified according to their drug exposure, in three steps: Conversion of prescription data into exposure variables (using ATC‐DDD) Construction of individual trajectories of exposure Clustering of individual trajectories of exposure (using the R package Kml ) We applied this method to psychotropic drugs prescribed during pregnancy. The present study involved women, included in the EFEMERIS database, who gave birth in Haute‐Garonne (France) between 2004 and 2010 ( N = 54 918). Results: Exposure to psychotropic drugs of 3708 pregnant women was studied (6.7%). The pregnant women could be classified into four groups with homogeneous trajectories of exposure: low constant exposure during pregnancy (Cluster A: 70.8% of women); decreasing exposure during the first trimester of pregnancy and low constant exposure thereafter (Cluster B: 19.6%); moderate constant exposure (Cluster C: 8.2%); and high albeit decreasing exposure (Cluster D: 1.4%). Conclusions: The proposed new method enabled us to describe more precisely women's exposure to drugs during pregnancy, and to distinguish different profiles of exposure. This method could be used to investigate specific outcomes related to duration and intensity of drug exposure during pregnancy, and also to study adverse drug reactions throughout life. Copyright © 2016 John Wiley & Sons, Ltd.